An Investigation of Teachers’ Perspectives on Favoritism in Schools: Implications for Educational Policy and Practice - Bayram, Ismail; Duyar, Yakup; Karakose, Turgut; Kaplan, Halil İbrahim (Education process: international journal, 2024)
Background/purpose. In the literature, favoritism is often discussed as a form of corruption and an unethical practice. Studies related to favoritism in educational organizations have found that favoritism negatively impacts educational institutions. This study aims to investigate how teachers defined and perceived favoritism at school as well as their views on preventing such acts by the school principal. Materials/methods. A qualitative, phenomenological approach was used in the study. Data was collected from forty-five teachers who had previously been exposed to acts of favoritism using a semistructured interview form. Participants were selected using a purposive, criterion-based sampling method. Data was analyzed using descriptive and content analysis. Results. The results indicated that teachers defined favoritism as preferential and unfair treatment of people based on personal interests, friendship, gender, kinship, political views, union affiliation, teaching subject, professional experience, or race. The participants reported that school principals practiced favoritism through their choice of adjustments to class schedules and duty days, unfair distribution of extra duties, unfair response to leave requests, being unfair in tolerating mistakes, allowing for flexible class entry and exit times, or modifications to class assignments. To prevent such practices, the teachers suggested that the criteria for becoming a principal be regulated to ensure merit-based appointments and democratic management in addition to providing in-service training and supervision. They also suggested that school principalship should be subject to rotation to avoid acts of favoritism. Conclusion. These results indicate that school principals should be appointed using more objective criteria so that factors such as union affiliation and political views are not prioritized over merit. Teachers and school principals’ awareness of favoritism and its negative results could also be raised by providing in-service training and explicit norms to support justice in schools.